Telementoring versus face-to-face mentoring in the training of scleral fixation surgery of intraocular lenses. - Luiz Filipe Adami Lucatto; Juliana Moura Bastos Prazeres; Gabriel Castilho Sandoval Barbosa; Eduardo Amorim Novais; Ricardo Luz Leitão Guerra; Emmerson Badaró; Luiz Henrique Soares Gonçalves de Lima; Eduardo Buchele Rodrigues (PLoS ONE, 2023)
Purpose To assess telementoring as a complementary tool for surgical training of a scleral fixation technique. Design Randomized, controlled, two-arm, blinded clinical trial. Methods Using a 3D visualization system, 132 participants were randomized in order of enrollment into traditional face-to-face mentoring (n = 66) and telementoring (n = 66). A single surgeon mentored all participants in the 2 groups. The procedure was performed in a model suitable for training in intraocular lens fixation SimulEYE® (INSEYET, WESTLAKE VILLAGE, CA, USA). In the telementoring group, the images captured on a local computer were sent to a second computer located in another room through a teleconferencing platform in real-time. Nine steps of the recorded procedure were evaluated and scored by two masked independent surgeons experienced in the technique. Main outcomes measures The primary outcomes evaluated were the global score (the sum of each score on the rubric), surgical failure, and surgical time (in seconds). Results Surgical success was achieved in 98.5% in the face-to-face group and in 95.5% in the telementoring group (p-value = 0.619). Minimal technical problems were reported in 8 procedures in the telementoring group (12%), without interfering with the surgical result, and completion of the procedure. Conclusions Telementoring is an encouraging educational tool that can overcome geographical barriers to ease the transfer of abilities and knowledge. We lack evidence in terms of group differences for superiority comparing face-to-face and telementoring, in addition to presenting comparable results regarding surgical success and failure. More studies are needed to explore the impact of telementoring in other ophthalmological surgeries. Trial registration The Federal University of São Paulo institution's Research Ethics Committee reviewed and approved this study protocol (approval number, 5.383.484).